Analisis Pengaruh Modifikasi Penukar Panas Terhadap Efisiensi Pendinginan Oli Gearbox Separator pada Pabrik Semen - Iskandar, Norman; Aritonang, Riventus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
Inside the cement factory, there is a finish mill which functions for the mixing process between clinker and gypsum to be used as cement. In that section there is a separator that functions to separate the finished cement and cement that still requires a re-milling process. In the separator there is a separator rotor which has a role to separate cement according to the size of the granulation so that those with standard sizes can be easily pushed by the circulating air fan and brought to the cement silo. The separator rotor is rotated by a motor which is passed by the gearbox as the transmission system. In order for the gearbox to work optimally, oil with certain temperature conditions is needed. Over time, the oil will become hot and cannot work effectively, so an oil cooling system is installed in this system. The oil cooler is a heat exchanger with water cooling fluid. This study aims to apply the NTU (Number of Transfer Units) method, in order to obtain an efficient and suitable heat exchanger working system as an oil cooler. The results obtained are an increase in efficiency of 2.74% from 35% to 37.74%.